Making preparation of poultry and eggs safer for consumers: a focus on recipes and temperature - Maughan, Curtis A. J. (Kansas State University, 2015)
Consumer food safety often is lacking, with many studies showing that we need to understand consumer behavior better and find new ways to provide information. The objective of this research was to better understand consumer food safety behaviors, find possible avenues for communicating food safety instructions to consumers, and determine how those avenues could work for demonstrating food safety today. Results from this research showed that two of the main potential avenues for communicating food safety instructions, namely recipes and cooking shows, were wholly lacking in good information and behaviors. A survey of egg dish recipes found that almost none contained temperature information, despite recommendations of food safety agencies. Observing celebrity chefs prepare food showed that every chef repeatedly had poor food safety practices which would lead to foodborne illness if followed by consumers at home. Two consumer studies were done with observers watching consumers prepare poultry and egg items. In the first study, consumers were asked to prepare poultry and egg items using both stovetop and oven methods. This study demonstrated that consumers do not follow many food safety behaviors, such as hand washing and using thermometers, and that those who used a thermometer were not better at reaching a safe temperature than those who didn’t use one. The second study had consumers prepare poultry items following a recipe, with half receiving food safety instructions on hand washing and thermometer use with their recipes. This study demonstrated that the addition of food safety instructions dramatically improved food safety behaviors in consumers. A separate study looked at the effect of changing lighting due to recent changes in efficiency regulations. This study found that some forms of modern lighting, such as LEDs, are more likely to make consumers think that poultry products are finished cooking before they are done, showing an even greater need for thermometer use. These studies present a message for the industry: food safety information and behaviors are lacking in consumers, but simple efforts such as adding food safety instructions to recipes can make consumers more aware of appropriate behaviors and improve their food safety.
Keywords: Food safety; Consumer behavior; Poultry; Eggs; Food Science (0359)